PERAN GURU PAI DALAM PEMBINAAN MENTAL SPIRITUAL SISWA DI MTs NUSANTARA SUMBERTAMAN PROBOLINGGO - Maryam Yulianti; Benny Prasetiya (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
Education is a person's conscious effort to seek knowledge and experience that initially did not know to know. Teachers as the main actors in the implementation of education have a very important role in achieving educational goals. Spiritual mental development of students is very important in order to fortify students so that they are not easily affected by negative things. PAI teachers play an important role in developing students' mental and spiritual development. The purpose of this study: to determine the role of PAI teachers in fostering the mental and spiritual development of students at MTs Nusantara Sumbertaman Probolinggo. This study used descriptive qualitative data collection methodology interviews, observations and documents. The data source used is primary by interviewing school principals, PAI teachers, and student guardians. The results of this study indicate that the role of PAI teachers in mental-spiritual development is very important for students at MTs Nusantara. The forms of mental and spiritual development of students at MTs Nusantara are discipline, giving directions about science, teaching students to care about the environment and getting used to praying in congregation.